Persecuted [videorecording (DVD)]. - Remar, James; Davison, Bruce, 1946-; Thompson, Fred, 1942-2015 ([Publisher not identified], 2014)
Nationally acclaimed evangelist John Luther is the last obstacle in the way of sweeping religious reform in the States. When a U.S. Senator frames him in the murder of an innocent girl, an era of persecution is unleashed. Out on bail, Luther escapes surveillance in search of the truth. Luther vows to expose anyone involved with the girl's murder. It's a mission that brings him face-to-face with the coming storm of persecution that will threaten the entire Christian community in America.